Doença falciforme e atividade laboral - Pires, Rosana Paula (2019)
This study, which evaluated the impact of sickle cell disease on the work activity of people with the condition and the public health care provided in the city of Uberlândia / MG to these people, allowed us to conclude that the DF has an important negative impact on the work situation resulting in a high social cost and that access and quality of care provided by the Primary Health Care network and the Urgency and Emergency Network need to be improved and this improvement is directly related to the training of health teams. We observed that only 28.1% of the study participants of working age were working, that the per capita monthly income of the vast majority (93.7%) was extremely low (≤ one minimum wage), with 9.4% of people extreme poverty and 28.1% in poverty and that only a small minority (3.1%) had their own home. In relation to public health care, we found that about 44.0% of people with SCD were not included in the Primary Health Care network, which did not provide several procedures / actions recommended by the Ministry of Health. About 94.0% were dissatisfied / partially satisfied with the emergency care provided in the Integrated Care Units (UAIs) and the main reasons for this dissatisfaction were ignorance of the DF by the health team (87.5%), delay in care (81.3%) and inadequate conduct by the health team (59.5%). We hope that the main contributions of the study are the awareness of public administrators in relation to the implementation of social policies that minimize the negative impact of socioeconomic factors on the quality of life of people with SC and state and municipal health managers so that they undertake efforts in the field. to provide continuing education in sickle cell disease to their health teams, so that they can fulfill their role of providing comprehensive and quality health care.